Predicting Growth Mindset: The Roles of Ambiguity Tolerance and Competence Beliefs in High School Students - Sadeghi, Jamal; Jalalian, Zahra Sadat; Mousavinejad, Meysam; Bagheri, Saghar; Peyvastegar, Marzieh; Rashidpour, Roya (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to investigate the relationship between growth mindset, ambiguity tolerance, and competence beliefs among high school students in Tehran. Methodology: A cross-sectional design was utilized, with a sample of 219 high school students from Tehran selected based on the Morgan and Krejcie table for adequate power. Participants completed the Mindset Assessment Profile (MAP) for growth mindset, the Multiple Stimulus Types Ambiguity Tolerance Scale-II (MSTAT-II) for ambiguity tolerance, and the Perceived Competence Scale for Children (PCS-C) for competence beliefs. Descriptive statistics, Pearson correlation analysis, and linear regression were conducted using SPSS-27 to analyze the data and identify significant relationships between the variables. Findings: The analysis revealed significant positive correlations between growth mindset and both ambiguity tolerance (r = 0.42, p < 0.01) and competence beliefs (r = 0.47, p < 0.01). The linear regression analysis indicated that ambiguity tolerance and competence beliefs collectively explained 39% of the variance in growth mindset (R² = 0.39, F(2, 216) = 69.02, p < 0.001). Both predictors were found to be significant, with competence beliefs showing a slightly stronger influence (β = 0.37, p < 0.001) compared to ambiguity tolerance (β = 0.34, p < 0.001). Conclusion: The findings suggest that both ambiguity tolerance and competence beliefs are important predictors of growth mindset among high school students. These results underscore the need for educational interventions that foster these psychological traits to promote a growth mindset, which can lead to improved academic outcomes and personal development. The study contributes to the broader understanding of how mindset beliefs are shaped and offers practical implications for educators and policymakers.